Application of Ta'widh and Gharamah in Islamic Banking in Malaysia - Muneeza, A.; Zainudin, N. A.; Ali, R.; Ibrahim, S. N.; Mustapha, Z. (Universiti Sains Islam Malaysia, 2024)
The objective of this paper is to explore the practical application of ta’widh and gharamah in Islamic banking in Malaysia with reference to the guidelines that are applicable to date; and find out the issues detected in the implementation of them. In the course of doing this, Shariah reasons for imposing ta’widh and gharamah in Islamic banking are discussed. Also, whether ta’widh and gharamah would be required for Islamic banking with reference to possible alternatives to them is also discussed. This qualitative study primarily focuses on library research and adopts case study approach for analyzing the application of ta’widh and gharamah. The jurisdiction of the study is Malaysia because the central bank of the country has made policies on the matter. The paper draws on observations made by Shariah scholars about the policies on the subject matter. This study gives an insight into the history and issues related to ta’widh and gharamah which are often kept tacit. It is recommended that future studies should look into the effectiveness of these two approaches to serve as a deterrent factor and contribute to the declining rate of non-performing financing in Islamic banks.